2019
DOI: 10.1177/0272989x19874347
|View full text |Cite
|
Sign up to set email alerts
|

Do Shared Decision-Making Measures Reflect Key Elements of Shared Decision Making? A Content Review of Coding Schemes

Abstract: Background. There is a growing need for valid shared decision-making (SDM) measures. We aimed to determine whether the items of extant SDM observer-based coding schemes assess the 4 key elements of SDM. Methods. Items of SDM coding schemes were extracted and categorized. Except for the 4 key elements of SDM (fostering choice awareness, informing about options, discussing patient preferences, and making a decision), (sub)categories were created inductively. Two researchers categorized items independently and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…The fact that our RCVC-questions had higher correlations may be due to the fact that both observer and patient addressed the same questions/dimensions. We also note that, in a recent study reviewing the items of validated observer-based instruments of shared decision making, Kunneman et al 13 observed that some validated tools do not assess all key elements of shared decision making while others go beyond these key elements and also assess aspects of health care that are not specific to a particular decision making process (e.g., general communication skills).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The fact that our RCVC-questions had higher correlations may be due to the fact that both observer and patient addressed the same questions/dimensions. We also note that, in a recent study reviewing the items of validated observer-based instruments of shared decision making, Kunneman et al 13 observed that some validated tools do not assess all key elements of shared decision making while others go beyond these key elements and also assess aspects of health care that are not specific to a particular decision making process (e.g., general communication skills).…”
Section: Discussionmentioning
confidence: 84%
“…Different models of shared decision making reflect different included dimensions, 5 and measures of shared decision making overlap incompletely with each other. 13 While exploring how/whether the 2 validated tools may be measuring different things, we observed that both tools assess similar but also different shared decision making components (see Appendix 2). However, RCVCpatient and RCVC-observer, which each included the same 2 items, yielded a relatively low correlation, thus supporting the idea that patients may not have the same perspectives of shared decision making processes as external observers do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high status placed on scientific evidence in guiding medical decisions may lead to "cookbook medicine", thereby reinforcing to medical students and residents that there is only one way of dealing with a given clinical situation [16,45,46]. We propose that this deeply rooted positivist paradigm in medical science may help to explain the relatively small effects of training physicians in SDM skills on their decisionmaking behavior in subsequent consultations [47][48][49][50][51] or their adoption of the patient perspective [52]. It raises the question of how this positivist professional identity is being shaped in graduate and postgraduate medical education programs, and how an appreciation of the uniqueness of each patient's context, views and preferences can be fostered throughout the medical education continuum.…”
Section: Discussionmentioning
confidence: 98%